Human Reproduction - Bastawros, Hala (Open textbook library., 2024)
This open textbook is designed to provide a deep understanding of the biological and biomedical aspects of human reproduction, covering a wide range of topics from basic reproductive biology to clinical applications. The book starts with foundational knowledge and progresses to more advanced topics while also including real-world clinical orientation for practical contexts.